The law of the European Union - Kuijper, Pieter Jan; Amtenbrink, Fabian; Curtin, Deirdre; Witte, Bruno de; McDonnell, Alison; Bogaert, Stefaan Van den (Wolters Kluwer, 2018)
This book provides the most comprehensive and systematic account available of the law of the EC and the EU, including detailed description and commentary on the economic and monetary union.